System Of Problems Based On Competent Approach From Geometry In Academic Lyceums - Nigora Daukeyeva (Euro Asian Journal Publishing, 2024)
The article provides information on the importance of applying a competency based approach to solving problems in the field of geometry and competency issues.
Keywords: efficiency of education; competent approach; a common matter